Computer and Network Security Essentials - Daimi, Kevin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book introduces readers to the tools needed to protect IT resources and communicate with security specialists when there is a security problem. The book covers a wide range of security topics including Cryptographic Technologies, Network Security, Security Management, Information Assurance, Security Applications, Computer Security, Hardware Security, and Biometrics and Forensics. It introduces the concepts, techniques, methods, approaches, and trends needed by security specialists to improve their security skills and capabilities. Further, it provides a glimpse into future directions where security techniques, policies, applications, and theories are headed. The book represents a collection of carefully selected and reviewed chapters written by diverse security experts in the listed fields and edited by prominent security researchers.
Part I.COMPUTER SECURITY -- Chapter 1.Computer Security -- Chapter 2.A Survey and Taxonomy of Classifiers of Intrusion Detection Systems -- Chapter 3.A Technology for Detection of Advanced Persistent Threat in Networks and Systems Using a Finite Angular State Velocity Machine and Vector Mathematics -- Chapter 4.Information-theoretically Secure Privacy Preserving Approaches for Collaborative Association Rule Mining -- Chapter 5.A Postmortem Forensic Analysis for a JavaScript Based Attack -- Part II. NETWORK SECURITY -- Chapter 6.Malleable Cryptosystems and Their Applications in Wireless Sensor Networks -- Chapter 7. A Survey and Taxonomy on Data and Pre-processing Techniques of Intrusion Detection Systems -- Chapter 8. Security protocols for networks and Internet: A global vision -- Chapter 9. Differentiating Security from Privacy in Internet of Things-A Survey of Threats and Solutions -- Chapter 10. Reliable Transmission Protocol for Underwater Acoustic Networks -- Chapter 11. Using Sports Plays to Conﬁgure Honeypots Environments to form a Virtual Security Shield -- PART 3: CRYPTOGRAPHIC TECHNOLOGIES -- Chapter 12.Security Threats and Solutions for Two Dimensional Barcodes: A Comparative Study -- Chapter 13. Searching Encrypted Data on the Cloud -- Chapter 14. A Strong Single Sign on User Authentication Scheme without Verifier Table for Cloud Based Services -- Chapter 15.Review of the Main Security Threats and Challenges in Free-Access Public Cloud Storage Servers -- Chapter 16.Secure elliptic curves in Cryptography -- Chapter 17.Network models for malware propagation in Wireless Sensor Networks: An Analysis -- PART 4: BIOMETRICS AND FORENSICS -- Chapter 18. Biometric Systems for User Authentication -- Chapter 19. Biometric Authentication and Data Security in Cloud Computing -- Chapter 20. Approximate Search in Digital Forensics -- Chapter 21.Privacy Preserving Internet Browsers - Forensic Analysis -- Part v. HARDWARE SECURITY -- Chapter 22. Experimental Digital Forensics of SubscriberIdentification Module (SIM) Card -- Chapter 23. A Dynamic Area-Efficient Technique to Enhance ROPUFs Security against Modeling Attacks -- Chapter 24. Physical Unclonable Functions (PUFs) Design Technologies: Advantages and Trade Offs -- PART 6. SECURITY APPLICATIONS -- Chapter 25. Generic Semantics Specification and Processing for Inter-System Information Flow Tracking -- Chapter 26. On Inferring and Characterizing Large-Scale Probing and DDoS Campaigns -- Chapter 27.Design of a Secure Framework for Session Mobility as a Service in Cloud Computing Environment -- PART 7: SECURITY MANAGEMENT -- Chapter 28. Securing the Internet of Things: Best Practices for Deploying IoT Devices -- Chapter 29. Cognitive Computing and Multiscale Analysis for Cyber Security -- Chapter 30. A Comparative Study of Neural Network Training Algorithms for the Intelligent Security Monitoring of Industrial Control Systems -- Chapter 31. Cloud Computing: Security Issues and Establishing Virtual Cloud Environment via Vagrant to Secure Cloud Hosts -- Chapter 32. A Survey and Comparison of Performance Evaluation in Intrusion Detection Systems -- Chapter 33. Accountability for Federated Clouds -- Chapter 34. A Cognitive and Concurrent Cyber Kill Chain Model -- Chapter 35.Defense Methods Against Social Engineering Attacks.
Keywords: Telecommunication; Computer networks .; Electronic digital computers -- Evaluation; Data protection; Communications Engineering, Networks; Computer Communication Networks; System Performance and Evaluation; Data and Information Security